Evidence for fumonisin inhibition of ceramide synthase in humans consuming maize‐based foods and living in high exposure communities in Guatemala. Issue 11 (3rd September 2015) - Riley, Ronald T.; Torres, Olga; Matute, Jorge; Gregory, Simon G.; Ashley‐Koch, Allison E.; Showker, Jency L.; Mitchell, Trevor; Voss, Kenneth A.; Maddox, Joyce R.; Gelineau‐van Waes, Janee B.
Abstract : Scope: Fumonisin (FB) occurs in maize and is an inhibitor of ceramide synthase (CerS). We determined the urinary FB1 (UFB1 ) and sphingoid base 1‐phosphate levels in blood from women consuming maize in high and low FB exposure communities in Guatemala. Methods and results: FB1 intake was estimated using the UFB1 . Sphinganine 1‐phosphate (Sa 1‐P), sphingosine 1‐phosphate (So 1‐P), and the Sa 1‐P/So 1‐P ratio were determined in blood spots collected on absorbent paper at the same time as urine collection. In the first study, blood spots and urine were collected every 3 months (March 2011 to February 2012) from women living in low (Chimaltenango and Escuintla) and high (Jutiapa) FB exposure communities (1240 total recruits). The UFB1, Sa 1‐P/So 1‐P ratio, and Sa 1‐P/mL in blood spots were significantly higher in the high FB1 intake community compared to the low FB1 intake communities. The results were confirmed in a follow‐up study (February 2013) involving 299 women living in low (Sacatepéquez) and high (Santa Rosa and Chiquimula) FB exposure communities. Conclusions: High levels of FB1 intake are correlated with changes in Sa 1‐P and the Sa 1‐P/So 1‐P ratio in human blood in a manner consistent with FB1 inhibition of CerS.